IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA KEARIFAN LOKAL DI SMP GEMA 45 SURABAYA - Kurniawati, Eva; Halima, Nur (Jurnal Manajerial Bisnis, 2024)
This study aims to describe the implementation of the project to strengthen Pancasila student profile of local wisdom at SMP Gema 45 Surabaya. The focuses of this research are: project implementation, project supporting factors, project inhibiting factors, and solutions to project inhibiting factors. This research is a descriptive qualitativeresearch. The results of this study describe that the implementation of the project to strengthen the Pancasila student profile of local wisdom at SMP Gema 45 Surabaya was carried out through a process of planning, managing and reporting project results. Project planning is carried out through the stages of: forming a project facilitator team, identifying the stages of education unit readiness in carrying out the project, determining project dimensions and themes, designing project time allocations, compiling project modules, determining project learning objectives, and developing topics, activity flow, and project assessment. Management of the project to strengthen the Pancasila student profile of local wisdom is carried out by initiating project activities, optimizing project implementation, closing a series of project activities, and optimizing partner involvement. The report on the results of the project to strengthen the Pancasila student profile of local wisdom is carried out by collecting and processing the results of the assessment, and compiling a project report card.